Surface engineered lipid nanoparticle-mediated site-specific drug delivery system for the treatment of inflammatory bowel disease. (5th November 2018) - Sinhmar, Gurpreet Kaur; Shah, Neel N.; Rawal, Shruti U.; Chokshi, Nimitt V.; Khatri, Hiren N.; Patel, Bhoomika M.; Patel, Mayur M.
Abstract: The major challenge for the treatment of inflammatory bowel disease (IBD) is the incompetence to deliver the drug molecule selectively at the site of inflammation. Taking this into consideration, we proposed development of mannosylated nanostructured lipid carrier system (Mn-NLCs) for active targeting and site-specific delivery of budesonide to the inflamed tissues. The developed Mn-NLCs were characterized for particle size and size distribution, zeta potential, %entrapment efficiency, FTIR and TEM analysis. Furthermore, to ensure delivery of developed cargo to the colonic region, the Mn-NLCs were encapsulated using Eudragit ® S100 coated pellets. The in vivo evaluation of developed system was performed by employing oxazolone colitis rat model. The average particle size of Mn-NLCs (301.7 ± 2.88 nm) was found to be more than that of unconjugated NLCs (284.0 ± 4.53 nm) with marginally reduced % entrapment efficiency (90.88 ± 3.86%). The in vitro cytotoxicity studies using J774A.1 cell line revealed that Mn-NLCs were non-toxic as compared to pure drug. The in vivo evaluation depicted that Mn-NLCs showed significant reduction in clinical activity scoring, macroscopic and microscopic indexing, colonic myeloperoxidase activity and inflammatory cytokines. In conclusion, the developed Mn-NLCs appear to be promising for the treatment of IBD by selectively targeting inflamed colonic region as compared to unconjugated nanoparticulate system. Graphical Abstract: